The formation process and responsive impacts of single oil droplet in submerged process. Issue 1 (15th November 2017) - Li, Haoshuai; Meng, Long; Shen, Tiantian; Zhang, Jianrui; Bao, Mutai; Sun, Peiyan
Abstract: Simulated column was applied to research forming progress of single oil droplet in submerged process, floating progress, and study effects of environment factors and dispersants on the concentration of oil hydrocarbon in water as well as changing rules of oil droplet sizes. As expected, particular formation mechanism of single oil droplet was presented. When necking down length L is 0.5 time of oil droplet diameter (d) after expansion phase, necking down becomes long and thin; when L = 2 d, necking down begins to break. In floating progress, the shape changes oval and its motion trail becomes an auger-type. Fluctuation occurs at horizontal direction. Dispersants decrease oil droplet size by its dispersion effect, and cut down effect of Van Der Waals force among oil droplets. More broadly, these findings provide rare empirical evidence expounding formation mechanism of single oil droplet to increasing ability of oil spill response. Graphical abstract: Highlights: The particular formation mechanism of single oil droplet was presented. The oil particle formation depends on necking down length and droplet diameter. The shape changes oval and its motion trail becomes an auger-type. Dispersants can cut down effect of Van Der Waals force among oil droplets.